Terfezia boudieri: A Desert Truffle With Anticancer and Immunomodulatory Activities - Al Obaydi, Maha Farid; Hamed, Wafaa M.; Al Kury, Lina T.; Talib, Wamidh H. (Frontiers in Nutrition, 2020)
ABSTRACT Desert truffles have high nutritional value and grow wild in the Mediterranean basin and Western Asia. Although, many studies were performed to evaluate truffles nutritious values and phytochemical composition, studies are limited to evaluate their anticancer and/ or immunomodulatory effects. Our study was conducted to evaluate the anticancer and immunomodulatory effects of Terfezia boudieri (desert truffle). Different solvent extracts were prepared from the truffle and MTT assay was used to measure their anticancer activity against different cancer cell lines . Total phenolic content in each extract was determined by using Folin-Ciocalteu reagent and qualitative phytochemical screening was performed . The degree of apoptosis induction (using caspase 3 assay) and vascular endothelial growth factor expression were detected using standard kits. Also, ELISA was used to measure levels of IFN- γ, IL-2, IL-4 and IL-10 secreted by splenocytes . The effect of the extracts on splenocytes proliferation was measured using MTT assay. Macrophage function was evaluated using nitro blue tetrazolium assay and pinocytosis function was evaluated using neutral red method. Terpenoids, phytosterols and carbohydrates were present in all extracts, while tannins, alkaloids and flavonoids were detected only in aqueous/methanol and aqueous extracts. The highest total phenolic content was observed in aqueous and aqueous methanol extracts. N-hexane extract was the most potent against most cancer cell lines. Aqueous/methanol extract showed high apoptosis induction and angiogenesis suppression effects. An increase in TH1 cytokines (IFN- γ, IL-2) level and a decrease in TH2 cytokine (IL-4) level were evident after lymphocytes stimulation by aqueous/methanol, n-hexane and ethyl acetate extracts of T. boudieri. Ethyl acetate extract of T. boudieri were the most potent extracts to stimulate lymphocytes proliferation while all other extracts showed moderate stimulation. Aqueous/methanol extract was the most active extract to stimulate phagocytosis. Ethyl acetate extract was the most active extract to stimulate pinocytosis. The use of T. boudieri provides variable health benefits. N-hexane, ethyl acetate and aqueous/methanol extracts exhibited anticancer activities and are potent stimulators of innate and acquired immunity. Further testing is needed to identify the biologically active compounds and detect them quantitatively.